Hunger, whiteness and religion in neoliberal Britain : an inequality of power - Power, Maddy (Policy Press, 2022)
Exploring why food aid exists and the deeper causes of food poverty, this book addresses neglected dimensions of traditional debates. It challenges neoliberal governmentality and shows how food charity maintains inequalities of class, race, religion and gender.